Genetic characterization of the Moxotó goat breed using RAPD markers - Oliveira, Rejane Rodrigues de; Egito, Andréa Alves do; Ribeiro, Maria Norma; Paiva, Samuel Rezende; Albuquerque, Maria do Socorro Maués; Castro, Silvia Ribeiro; Mariante, Arthur da Silvia; Adrião, Manuel (Pesquisa Agropecuaria Brasileira, 2005)
The objective of this study was to verify the genetic diversity between and within seven populations of Moxotó goat (n = 264) from the States of Pernambuco, Paraíba and Rio Grande do Norte, using RAPD (Random Amplified Polymorphic DNA). Moxotó, as well as other naturalized breeds, suffers genetic losses due to the indiscriminate miscegenation with breeds raised in the Northeast Region of Brazil. The genetic characterization of these genetic resources is essential to conservation and breeding programs. DNA was extracted from lymphocytes using a non-organic protocol. The 16 primers used were selected from 120 decamer oligonucleotide primers and generated 56 polymorphic bands. The analysis of molecular variance (AMOVA) showed that the greater part of total genetic variability (71.55%) was due to differences between individuals within populations, while 21.21% was among populations. The analysis of variance among the pairs of populations demonstrated that the populations located in Floresta, PE x Angicos, RN presented a smaller value of intrapopulational differentiation (8.9%), indicating low genetic variability among them. Nei's genetic distances varied between 0.0546 and 0.1868 in the populations. The dendrogram generated showed that the Canindé breed, used as outgroup, clustered with the populations of Moxotó, indicating a possible common origin of the naturalized goat breeds.